Exploring the future of GM technology in sustainable local food systems in Colombia - Cárdenas Pardo, Néstor Julián; Rodriguez Robayo, Dolly Esperanza; Fernandez Lizarazo, John Cristhian; Peña-Quemba, Diego Camilo; McGale, Erica (Frontiers in Genome Editing, 2023)
The security of Earth’s food systems is challenged by shifting regional climates. While agricultural processes are disrupted by climate change, they also play a large role in contributing to destabilizing greenhouse gases. Finding new strategies to increase yields while decreasing agricultural environmental impacts is essential. Tropical agriculture is particularly susceptible to climate change: local, smallholder farming, which provides a majority of the food supply, is high risk and has limited adaptation capacity. Rapid, inexpensive, intuitive solutions are needed, like the implementation of genetically modified (GM) crops. In the Latin American tropics, high awareness and acceptance of GM technologies, opportunities to test GM crops as part of local agricultural educations, and their known economic benefits, support their use. However, this is not all that is needed for the future of GM technologies in these areas: GM implementation must also consider environmental and social sustainability, which can be unique to a locality. Primarily from the perspective of its educators, the potential of a rural Colombian university in driving GM implementation is explored, including the role of this type of university in producing agricultural engineers who can innovate with GM to meet regionally-dependent environmental and cultural needs that could increase their sustainability.